IDENTITAS DALAM NOVEL MARYAM KARYA OKKY MADASARI - Eka Ugi Sutikno; Ahmad Supena (Universitas Sultan Ageng Tirtayasa, 2016)
Maryam has a strong foundation for criticizing the discrimination experienced by The Indonesian Ahmadiyah Assembly (JAI). This paper seeks to provide objective information regarding his time and he tried to represent that between the real world and the world realitistik novel can be very coherent. The goal is to know and to understand the identity and political identity was revealed in the novel of Maryam by Okky Madasari. The results showed that identity in the novel of Maryam by Okky Madasari has met with the complexity when the conflict between the subject's identity JAI of passive and active subject's identity, the ‘Islamist-Tier’, and between subjects who wanted her identity and subjects does not want diversity.